2018
DOI: 10.1007/s11605-018-3789-7
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Drainage and Amylase Measurement for Detection of Leakage After Gastrectomy for Gastric Cancer

Abstract: Daily amylase measurement in drain fluid does not influence the early recognition and management of leakage in gastric cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Study characteristics of the included studies are shown in Table 1. The role of systemic biomarkers was evaluated separately in fifteen studies, [32,33,34,35,36,37,38,39,40,41,42,43,44,45,46] drain fluid in nine [33,44,45,46,47,48,49,50,51], combined scoring systems in three studies [35,41,52], and mediastinal microdialysis [53], urine volatile organic compounds [54] and respiratory index [40] were all evaluated in one study. All studies except three [37,53,54] were retrospective.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study characteristics of the included studies are shown in Table 1. The role of systemic biomarkers was evaluated separately in fifteen studies, [32,33,34,35,36,37,38,39,40,41,42,43,44,45,46] drain fluid in nine [33,44,45,46,47,48,49,50,51], combined scoring systems in three studies [35,41,52], and mediastinal microdialysis [53], urine volatile organic compounds [54] and respiratory index [40] were all evaluated in one study. All studies except three [37,53,54] were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…Various definitions of AL were found in the included studies, as shown in Table 2. Six studies [40,42,43,45,49,50] did not mention the median or range concerning the day of AL diagnosis. In the remaining eighteen studies AL was diagnosed with a median on POD 7, ranging between 1 and 30 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, randomization was never mentioned in one of the four articles, classi ed as RCTs. After 2015 other retrospective studies have been published, but most of them included small number of patients and heterogeneous types of surgery, including multi-visceral and R2 resection [5,6,7,8]. Our study group recently published an updated metanalysis including both RCTs and cohort studies comparing the use of prophylactic drain with drain avoidance [9].…”
Section: Background and Rationalementioning
confidence: 99%